Short Communication: Genetic diversity among Fusarium isolates from cereals in Iran assessed using RAPD marker - SARA SIAHPOUSH; MOSTAFA DARVISHNIA (Society for Indonesian Biodiversity, 2019)
Siahpoush S, Darvishnia M. 2019. Short Communication: Genetic diversity among Fusarium isolates from cereals in Iran assessed using RAPD marker. Biodiversitas 20: 292-296. Fusarium species cause important disease on many crops including cereals, and accurate identification and then proper management of this disease will be helpful to reduce economic losses. In this paper, 13 Fusarium isolates from root and crown of cereals in western Iran were identified by morphological and molecular methods. Sequencing of translation elongation factor 1-alpha revealed 8 species as follows: Fusarium acuminatum, F. avenaceum, F. culmorum, F. equiseti, F. proliferatum, F. reticulatum, F. solani, and F. tricinctum. Species diversity was analyzed by random amplified polymorphic DNA (RAPD). Four primers were used as Rfu9, Rfu10, Rfu23, and Rfu25 which all of them produced distinct and reproducible bands. A dendrogram was developed by UPGMA. Generated polymorphic bands were observed in all 13 different species by 4 primers. Rfu9 by 13 bands and Rfu23 by 10 ones, produced the most and the least bands respectively. Genetic similarity coefficient was between 0.00-0.9. RAPD analysis showed that these isolates were genetically varied and two clusters were formed with Fusarium isolates.